Calculation of optimal values of weight coefficients for compensation of the mutual coupling of antenna array elements - Anatoly M. Bobreshov; Alexander A. Kononov; Olga V. Neskorodova; Ksenia V. Smuseva; Grigory K. Uskov (Физика волновых процессов и радиотехнические системы)
Background. Antenna arrays are widely used in a variety of modern radio engineering systems for wireless communication and radar. The phenomenon of mutual coupling of antenna elements, which is manifested in practical implementation, may cause noticeable distortions of one of the most important characteristics of the antenna array – its radiation pattern, which must meet strict requirements in certain tasks. In view of this, the relevance of the question of methods for achieving the most accurate control of radiation patterns becomes clear. Aim. Investigation of the possibility of compensating the mutual coupling of antenna elements by adjusting the weight coefficients at the input of the antenna array, derivation of calculation relations for converting input signals, evaluation of performance measures for reducing distortion of directional characteristics provided by the application of the proposed approach. Methods. The main theoretical relations were derived using a mathematical apparatus that allows applying linear algebra methods to the description of the mutual coupling of antenna elements. The study of the antenna arrays based on half-wave dipoles and considered as an example was carried out using electrodynamic modeling. Quantitative estimates of the effects of mutual coupling and their compensation, as well as verification of the developed mathematical model, were carried out using numerical methods. Results. On the basis of the analysis of matrix equations describing the mutual coupling of antenna elements, the possibility of performing the input signals transformation, providing the restoration of the radiation patterns characteristics as a result of the radiated electromagnetic waves interference, has been established. The basic mathematical relations necessary for the implementation of this procedure are derived, specific examples are considered and numerical accuracy characteristics of the proposed approach are obtained. Conclusion. The developed technique makes it possible to find the explicit form of the correcting linear transformation of input signals for an arbitrary antenna array. At the same time, the use of the correction matrix calculated in this way makes it possible not only to significantly reduce the distortion of the radiation patterns themselves caused by the mutual coupling of the antenna elements, but also to compensate for undesirable changes in such characteristics as the direction of the main beam of the antenna array.